Analysis of quasistatic squeeze behavior of magnetorheological fluid from the microstructure variations. (November 2021) - Luo, Qi; Wang, Yongqing; Liu, Haibo; Wang, Junpeng; Li, Yapeng; Li, Te
Magnetorheological fluid is a novel functional material, of which quasistatic squeeze behavior needs to be quantitatively controlled in industrial applications. Since the quasistatic squeeze behavior has a close relation with microstructure variations, thus it is modeled from a microscopic approach. By analyzing compression of single chains, aggregation from single chains to BCT structure and compression of BCT structure, the initial stressσ 0, yield stressσ y, yield strainε y, and stress in post-yield stageσ are respectively modeled. It is found that they have an exponential dependence on magnetic field strength H and particle volume concentrationξ, includingσ 0 ∝ ξ H 2, σ y ∝ H 2, and( σ y − σ 0 ) ∝ ξ 2, etc. By comparing predicted results with measured results, the micro-macro stress model on quasistatic squeeze behavior is well validated. This model can be used to design, manufacture, and control industrial magnetorheological devices.